A Literature Review: Transformational leadership style Analysis - Selvira Bawotong; Andi Indriani Ibrahim; Syahbudin Adam; Sahra S. T. Ali; Yuliana; Yuliana Tamsil; Zahra Aulia Tanjung (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The dramatic changes in the business environment due to globalization, technological advancements, and intensified competition have "forced" organizations to adapt, restructure, and innovate (Handoko & Tjiptono, 1996). This condition demands a specific, transformational leadership approach to overcome critical Human Resource (HR) challenges. These challenges include: a high turnover intention among employees, which increases recruitment costs (Suhakim & Badrianto, 2021); the necessity of managing the millennial generation workforce in the Industry 5.0 era (Alfian Fadilah & Kamilia, 2024); the relatively low performance of teachers in the education sector (Febriyanti, Zulaihati, & Sumiati, 2021); and low job satisfaction among nurses in the healthcare sector (Suweko & Dwiantoroa, 2020). Therefore, a "new" leadership concept is needed that can develop HR capacity to its highest potential. Transformational leadership is a highly relevant and effective model in various contexts of modern organizations, both in the business and educational sectors. This model is the key for leaders to develop the capacity and ability of human resources continuously. By focusing on inspirational motivation, skill development, collaboration, and individual attention, transformational leadership successfully creates an environment that supports individual growth, increases commitment, reduces turnover intention, and ultimately ensures the achievement of the organizational vision, goals, and sustained quality amidst dynamic changes.